Characterization of tetratricopeptide repeat-like proteins in Francisella tularensis and identification of a novel locus required for virulence - Dankova, Vera; Balonova, Lucie; Straskova, Adela; Spidlova, Petra; Putzova, Daniela; Kijek, Todd; Bozue, Joel; Cote, Christopher; Mou, Sherry; Worsham, Patricia; Szotakova, Barbora; Cerveny, Lukas; et al. (Infection and immunity, 2014)
Francisella tularensis is a highly infectious bacterium that causes the potentially lethal disease tularemia. This extremely virulent bacterium is able to replicate in the cytosolic compartments of infected macrophages. To invade macrophages and to cope with their intracellular environment, Francisella requires multiple virulence factors, which are still being identified. Proteins containing tetratricopeptide repeat (TPR)-like domains seem to be promising targets to investigate, since these proteins have been reported to be directly involved in virulence-associated functions of bacterial pathogens. Here, we studied the role of the FTS_0201, FTS_0778, and FTS_1680 genes, which encode putative TPR-like proteins in Francisella tularensis subsp. holarctica FSC200. Mutants defective in protein expression were prepared by TargeTron insertion mutagenesis. We found that the locus FTS_1680 and its ortholog FTT_0166c in the highly virulent Francisella tularensis type A strain SchuS4 are required for proper intracellular replication, full virulence in mice, and heat stress tolerance. Additionally, the FTS_1680-encoded protein was identified as a membrane-associated protein required for full cytopathogenicity in macrophages. Our study thus identifies FTS_1680/FTT_0166c as a new virulence factor in Francisella tularensis.
Keywords: Virulence; Animals; Genetic Loci; Mutagenesis, Insertional; Virulence Factors; Female; Francisella tularensis; makrofágy; ženské pohlaví; bakteriální proteiny; tularemie; Bacterial Proteins; Macrophages; genový knockout; Mice, Inbred BALB C; Tularemia; inzerční mutageneze; virulence; modely nemocí na zvířatech; myši inbrední BALB C; Disease Models, Animal; cytosol; Cytosol; zvířata; genetické lokusy; Gene Knockout Techniques; faktory virulence